Notebook [36, Fall 1995] - Leier, Mark (James Mark) (Labour/Le Travail, 1995)
Announces that records of the Laurentian University Faculty Association's 1989 strike have been deposited at the university's archives. Also announces a 60-page bibliography of British Columbia's labour history is available that was compiled by graduate students at Simon Fraser University. Briefly reported are recent conferences of the Pacific Northwest Labor History Association on labour and the environment (University of Oregon) and at the University of Northern British Columbia on new directions in BC history.